Blood Libel The Ritual Murder Accusation at the Limit of Jewish History - Johnson, Hannah R. (University of Michigan Press, 2012)
The ritual murder accusation is one of a series of myths that fall under the label blood libel, and describes the medieval legend that Jews require Christian blood for obscure religious purposes and are capable of committing murder to obtain it. This malicious myth continues to have an explosive afterlife in the public sphere, where Sarah Palin's 2011 gaffe is only the latest reminder of its power to excite controversy. Blood Libel is the first book-length study to analyze the recent historiography of the ritual murder accusation and to consider these debates in the context of intellectual and cultural history as well as methodology. Hannah R. Johnson articulates how ethics shapes methodological decisions in the study of the accusation and how questions about methodology, in turn, pose ethical problems of interpretation and understanding.